Pengaruh Motivasi, Disiplin Dan Kepemimpinan Terhadap Kinerja Karyawan Di PT. Bank BPD Bali Cabang Tabanan - Kepakisan, Bimantara (E-Jurnal Manajemen; Vol 3 No 2 (2014), 2014)
PT . Branch Bank BPD Bali Tabanan need encouragement , discipline and leadership that can guide employees in carrying out the work to be able to maximize the potential of employees that have an impact on employee performance. Not maximal performance of employees is also caused by some aspect that is not yet even granting taget, weak employee competency. Motivation, discipline and leadership influence on employee performance, which makes this research. The theory used the McClelland theory of achievement motivation and sample as many as 43 people. Interviews and questionnaires is a way to collect data. Multiple linear regression and Standardized Coefficients Beta testing is a technique of analysis used. From the results of analysis show that, 1 ) the partial motivation, discipline and leadership affect the performance of employees at PT. Branch Bank BPD Bali Tabanan. 2 ) simultaneously motivation, discipline and leadership affect the performance of employees at PT. Branch Bank BPD Bali Tabanan 3 ) the dominant variables affect the dependent variable is the variable motivation. Keywords : Motivation, Discipline, Leadership, Performance
Keywords: Motivation, Discipline, Leadership, Performance